2018
DOI: 10.1097/mpg.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress May Contribute to the Onset of Pediatric Inflammatory Bowel Diseases

Abstract: It is currently unclear whether seasonality affects the onset of inflammatory bowel diseases (IBDs: Crohn disease and ulcerative colitis) in children. Here, we examined the records of pediatric patients with IBD diagnosed between 2009 and 2015 in a discovery cohort of 169 cases and a validation cohort of 122 subjects, where the month of symptoms onset could be determined. No seasonal patterns could be identified in respect to conception, birth, and disease onset. An annual rhythm of symptomatic onset, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…For the time of birth analyses, no overall association with season or month of birth was found, somewhat in contrast to other [25][26][27][29][30][31][35][36][37]39,40] but not all studies [24,28,[32][33][34]38]. However, we did find that that the fortification policy might have been especially beneficial for individuals born in autumn.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…For the time of birth analyses, no overall association with season or month of birth was found, somewhat in contrast to other [25][26][27][29][30][31][35][36][37]39,40] but not all studies [24,28,[32][33][34]38]. However, we did find that that the fortification policy might have been especially beneficial for individuals born in autumn.…”
Section: Discussioncontrasting
confidence: 94%
“…Several studies have investigated the association between month or season of birth and IBD development with inconsistent results [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Month or season of birth can indicate different environmental exposures during gestation and infancy, e.g., sunshine hours as a proxy for vitamin D exposure, or infections, and/or use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…24 In a recent study, academic stress was implicated in the onset of IBD in susceptible children. 25 A previous study found that exposure to pets, especially dogs and cats protected against the development of IBD. 26 Similarly, a population-based Asian study by Ng et al 14 found that exposure to pet dogs and fish were protective factors for development of adult IBD.…”
Section: Discussionmentioning
confidence: 97%
“…The proposed pathophysiologic pathway includes that of the autonomic nervous system, hypothalamic–pituitary–adrenal axis, microbiota brain‐gut axis and the immune system 24 . In a recent study, academic stress was implicated in the onset of IBD in susceptible children 25 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers analyzed the relationship between the annual rhythm of IBD symptom onset and academic semesters in children. The results showed that academic stress may facilitate disease onset in pediatric IBD (82).…”
Section: Interaction Between Stress and Ibdmentioning
confidence: 98%